PEMBUATAN GAME INDONESIA MELAWAN SEKUTU - Andi Wijaya; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Indonesia Melawan Sekutu is a real-time strategy games which in the form of tower defense. This game also belong into educational game because the game provide player knowledge about history of Indonesian independence. The game is running well on computer that use Windows operating system. Indonesia Melawan Sekutu was created by Adobe Flash with Actionscript 3.0. This game consist of 6 chapters which have different difficulity. The result from testing phase that the game has good quality and increase knowledge players about Indonesian Independence